The battle for whole-child approaches: Examining the motivations, strategies and successes of a parents’ resistance movement against a performance regime in a local Norwegian school system - Skedsmo, Guri; Camphuijsen, Marjolein K. (Education Policy Analysis Archives, 2022)
In different parts of the world, social movements led by parents, educators, and professional organizations have emerged that resist educational standardisation and use of (high stakes) standardised tests, and that push for educational change. With the aim of extending empirical coverage of protest movements in non-English speaking countries, this study examines a Norwegian parental movement called Foreldreopprør i Osloskolen (FiO) (in English: Parental Uprising in the Oslo School). We draw on exploratory research based on in-depth interviews with initiators and members of FiO (n=8), as well as documentary and press analysis and an examination of social media sites. The analysis sheds light on the emergence and nature of the movement, parents’ main motivations and discourses, as well as the movements’ collective action strategies and main successes. The findings highlight how rather than opting-out their children from standardised tests, some Norwegian parents chose to opt-out their children from public schools, while continuing their fight for whole-child approaches in public education.